On the criteria for the severity of Infectious mononucleosis in hospitalized children - N. S. Pospelova; N. O. Postanogova; M. O. Satyukova; A. Yu. Deryusheva; A. V. Permyakova (LLC "Diagnostics and Vaccines", 2020)
Purpose of the study. Justification of the practical application of laboratory criteria marking the severity of infectious mononucleosis in hospitalized children.Materials and methods. A comparative prospective clinical study involved 54 children, aged 2 to 13 years, median age 5 years [3.0; 8.7]. The main study group consisted of 27 children with a severity of the disease, the comparison group - 27 patients of moderate. We used the Mann-Whitney test, Spearman's correlation coefficient and mathematical modeling.Results. The study found a direct correlative relationship between the severity of infectious mononucleosis and indicators of total and direct bilirubin, r = 0.39. «Cut of» values were determined: for total bilirubin ≥ 15 µmol / L, for direct bilirubin ≥ 5.5 µmol / L, sensitivity 96%, specificity 52%.Conclusions. «Cut of» bilirubin fractions can be used to predict the severity of infectious mononucleosis in hospitalized children on the first day of the disease.